Juízos reflexionantes e direito: em busca de uma ética hermenêutica crítica - Garcia, Jaci Rene Costa (Universidade do Vale do Rio dos Sinos, 2015)
The dissertation has the Kantian aesthetics as subject and proposes a study of reflecting judgment and its relation to critical hermeneutic ethics, having as main objective to investigate the role of aesthetics to the hermeneutics, its importance for the critical hermeneutic ethics and its possibility to offer epistemological basis for the Law in contemporaneity. The delimitation of the study involves: [i] an unified philosophical approach by the Kant's critical system which is able to identify the assumptions that allow the realization of judgments, [ii] the interception of understanding and the practical reason from the postulates of aesthetic judgment, especially the reflective judgment and [iii] speculate about the possibilities of a critical hermeneutics ethics serve as an epistemological guide to the Law. It was identified that it is possible to extend the reflecting judgment to the aesthetical field, even though the reflecting judgment is neither constitutive nor normative, once it contains a guiding function connected to the conformity principle to ends that serve as orientation for the cases evidenced in law area. In a synthetic way, the proposed discussion involves both determining and reflective judgments, being the first the difference, which permits the delimitation of the second, which ones are configured as helping lines to clarify the problem. The purpose, in this context, was to find a critical hermeneutical ethics that permits to undo the apparent antinomy between knowledge production, deduced from pure postulates, and the comprehension ever immersed in historicity and traversed by sensibility: these two moments, apparently opposite, can be overcome by the entireness and the unity of Kant’s work, allowing new perspectives for the comprehension of complex problems faced in the 21th century. In the second part of this work, it was elected Dworkin’s theory to confront the critical hermeneutic ethics, seeking to find, from the established interfaces, the position of aesthetic judgment in Dworkin’s model, in order to prove or disprove the hypothesis of the research. In this line, the analysis of reflective judgment and the route to the construction of a critical hermeneutic ethics are to find a new posture before the realities faced by the law since an epistemological orientation that will be possibly revealed by the research.
Keywords: Direito; Hermenêutica; Filosofia; Ética; Kant; Law; Hermeneutics; Philosophy; Ethics; ACCNPQ::Ciências Sociais Aplicadas::Direito